Peran Orangtua Dalam Menanamkan Etika Dengan Melatih Siswa Berbahasa Jawa Krama Di Sd Negeri Teguhan Sragen Tahun 2016/2017 - Yuani, Asih Syah, Drs.H.Mulyadi Sri Kamulyan, S.H, M.Pd (2017)
This study aims to describe 1) The Role of Parents in Inculcating Ethics to Students. 2) Describing the Role of Parents in Training the Javanese Krama Students. 3) Describing Students' Ability in Applying Javanese Krama In Everyday Life. 4) To describe the barriers parents experience in training students in Javanese Krama. In Sd Negeri Teguhan Sragen. The research method used is qualitative research with descriptive design. Data collection techniques used were interviews, observation, and documentation. The validity of the data is tested by using triangulation technique of source and technique. Data analysis used consisted of three stages: data reduction, data presentation, and conclusion. The results showed that 1) Parents play a role in instilling ethics in SDN Teguhan Sragen. 2) Parents play a role in training students of Javanese Krama. 3) Students Able to Speak Javanese Krama in everyday life. 4) Obstacles experienced is according to most parents is not easy because in today's more people who use the Indonesian language is seen as a national language. The solution of these barriers is to practice Little by little assisted by parents at home is by example when talking is the child will follow-speak speak Java Javanese Krama.